Constrained to be (im)mobile? Refugees' and Asylum seekers' practices to integrate in restrictive socio-economic urban contexts in Northern Italy - Dimitriadis, Iraklis; Ambrosini, Maurizio (Frontiers in Sociology, 2023)
This article comparatively examines forms of (im)mobility among refugees and asylum seekers (RAS) in coping with dispersal process, restrictive migration policies and local socio-economic characteristics in three cities of Northern Italy. Drawing on qualitative data, it sheds light on the everyday forms of (im)mobility of RAS to resist structural barriers limiting their opportunities to access jobs and welfare services. The Results show that people’s capacity to overcome barriers depends upon individual characteristics and informal networks, and is shaped by particularities of local contexts. While people’s regular legal status is considered an important resource in achieving goals, refugees and holders of international protection often have to adopt (im)mobility practices to access resources in contexts that do not facilitate their integration. This article highlights the inefficiency of integration and reception policies and advances the theoretical debate on the link between being (im)mobile and agency by calling authors to pay more attention to the (in)voluntary nature of spatial (im)mobility. Finally, it shows the ambivalent outcome of (im)mobilities in terms of agency, highlighting the implications for individuals before and during the COVID-19 pandemic.